181k views
0 votes
Make x the subject formula in the equation 3x + 6 - 3b​

User Dinei
by
4.0k points

2 Answers

2 votes

Answer:

x = b - 2

Explanation:

Given :

3x + 6 - 3b = 0

Subtract (6 - 3b) on both sides :

3x + 6 - 3b - (6 - 3b) = 0 - (6 - 3b)

3x + 6 - 6 + 3b - 3b = -6 + 3b

3x = 3b - 6

Divide throughout by 3 :

1/3 x 3x = 1/3 x (3b - 6)

x = b - 2

User Frohnzie
by
4.9k points
5 votes
  • 3x+6-3b=0
  • 3x-3b+6=0
  • 3(x-b)+6=0
  • 3(x-b)=-6
  • x-b=-6/3
  • x-b=-2
  • x=b-2

Done!

User Viktor Klang
by
5.4k points